Morphological Organization of the Dorsal Protuberance of Linepithema humile (Mayr, 1868) Ant's Larvae (Hymenoptera, Formicidae) - Bueno, Odair Correa [UNESP]; Camargo-Mathias, Maria Izabel [UNESP]; Ortiz, Gabriela [UNESP] (Wiley-Blackwell, 2011)
The Argentine ant Linepithema humile is an important invasive species because of the levels of infestation that it can reach; however, there is little information about its presence, histological organization, and function of the dorsal protuberance, which is found exclusively in their larvae. The objective of this study was to describe it in L. humile through scanning electron microscopy and transmission electron microscopy, bringing information about this structure. The epidermis of these larvae have cuticles covering the whole body, and is formed by a sequence of overlapping lamellas where the inner ones were thicker and presented lower electron density, whereas the outer ones were thinner and highly electron dense. Pores or pore-like channels were not observed. A thick and acellular region composed of granular material was found under the cuticular layer. Out of this region, the flattened epidermic cells formed an epithelial layer. For the dorsal protuberance region, these cells become prismatic, and similarly to the cuticle, presents significant thickening. These cells presented extended microvilli, as well as a great amount of lamellar rough endoplasmic reticulum. Under this epithelium was observed a concentration of fat body cells, more numerous in the dorsal protuberance region. This study indicated that the dorsal protuberance present in the first segment of L. humile larvae has apparently no secretory function because no pores were found. This fact allowed to conclude that in L. humile larvae the dorsal protuberance would have the function to make it easier for the worker ants to carry them within the colony. Microsc. Res. Tech. 74:551-558, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: ant; larvae; cuticle; dorsal protuberance; scanning electron microscopy; transmission electron microscopy (TEM)